Pemeliharaan Pada Mesin Moulding Unimat 22 A Di PT. Sejin Lestari Furniture - Repdhi Febriyan; Bagus Dwi Cahyono (Pusat Riset dan Inovasi Nasional, 2023)
Developments in the industrial world are increasingly rapid, resulting in increased competition in the industrial world, so that industrial companies are competing to improve production efficiency and effectiveness. Especially companies in the manufacturing sector, increasing productivity in a production system is an absolute thing that must be done. One of the main indicators in increasing productivity is the level of rehabilitation of production machines at the company. In measuring how good the rehabilitation of a production machine is, an effective and efficient maintenance maintenance process is needed for the company. Continuous use of the machine will decrease the level of readiness of the machine itself. In an effort to maintain the level of machine readiness so that production results are guaranteed due to continuous use of the machine, regular machine maintenance and maintenance activities are needed which are expected to prolong the condition of production machines so that they are not damaged, in case of machine damage it can disrupt production activities.